Sex beyond species: the first genetically analyzed case of intergeneric fertile hybridization in pinnipeds. Issue 2 (March 2016) - Franco‐Trecu, Valentina; Abud, Carolina; Feijoo, Matías; Kloetzer, Guillermo; Casacuberta, Marcelo; Costa‐Urrutia, Paula
SUMMARY: A species, according to the biological concept, is a natural group of potentially interbreeding individuals isolated by diverse mechanisms. Hybridization is considered the production of offspring resulting from the interbreeding of two genetically distinct taxa. It has been documented in over 10% of wild animals, and at least in 34 cases for Artic marine mammals. In Otariids, intergeneric hybridization has been reported though neither confirming it through genetic analyses nor presenting evidence of fertile offspring. In this study, we report the finding of a hybrid adult female between a South American fur seal ( Arctocephalus australis ) and a South American sea lion ( Otaria byronia ), and its offspring, a male pup, in Uruguay. Further based on morphological constraints and breeding seasons, sex‐biased hybridization between the two species is hypothesized. Morphological and genetic (nuclear and mitochondrial) results confirm de hybrid nature of the female‐pup pair. Here we discuss a genetic dilution effect, considering other hybridization events must be occurring, and how isolation mechanisms could be circumvented. Moreover, the results obtained from stable isotope analysis suggest feeding habits may be a trait transmitted maternally, leading to consider broader issues regarding hybridization as an evolutionary innovation phenomenon.